2008
DOI: 10.1073/pnas.0801048105
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interactions between the promoter and terminator regions of the mammalian BRCA1 gene

Abstract: The 85-kb breast cancer-associated gene BRCA1 is an established tumor suppressor gene, but its regulation is poorly understood. We demonstrate by gene conformation analysis in both human cell lines and mouse mammary tissue that gene loops are imposed on BRCA1 between the promoter, introns, and terminator region. Significantly, association between the BRCA1 promoter and terminator regions change upon estrogen stimulation and during lactational development. Loop formation is transcription-dependent, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 30 publications
1
122
1
Order By: Relevance
“…Gene Looping Accompanies Activated Transcription-Several yeast, mammalian, and viral genes have been shown to adopt a looped configuration during transcription (12)(13)(14)(15)(16)(17). We further demonstrated that the looping of galactose-inducible genes accompanied activated transcription and not the repressed or transcriptionally poised state of the gene (13).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Gene Looping Accompanies Activated Transcription-Several yeast, mammalian, and viral genes have been shown to adopt a looped configuration during transcription (12)(13)(14)(15)(16)(17). We further demonstrated that the looping of galactose-inducible genes accompanied activated transcription and not the repressed or transcriptionally poised state of the gene (13).…”
Section: Resultsmentioning
confidence: 77%
“…Accordingly, the termination factor-mediated loop at the mitochondrial rDNA transcription unit brought about efficient translocation of RNA polymerase from the terminator to the promoter, resulting in a 15-fold stimulation of transcription. The existence of similar gene loops has been recently reported for RNAP II-transcribed genes in yeast and mammalian cells (12)(13)(14)(15)(16). It has been shown that RNAP II-dependent gene looping is the consequence of the physical interaction of the terminator with the promoter of the same gene and is dependent on ongoing transcription.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, these studies showed that gene looping is dependent on components of the cleavage/polyadenylation machinery and the general transcription factor TFIIB. In mammals, gene looping has been proposed to regulate transcription of the human BRCA1 gene (Tan-Wong et al 2008). Additionally, Perkins et al (2008) showed the existence of gene looping at an integrated HIV-1 provirus, which required a functional poly(A) signal.…”
Section: Trans-acting Factor Dynamics At the Poly(a) Site Affect Tranmentioning
confidence: 99%
“…For this purpose, 3C assays were performed in estrogen-responsive MCF-7 cells and estrogen non-responsive MDA-MB-231 cells. But first the DNA looping of the GAPDH locus was evaluated to exclude a possible variation resulting from potentially differential enzymatic activity on different cellular DNAs (40). As evident in Fig.…”
Section: Tff Locus Is Delimited By Ctcf-bound Boundary Elements For Ementioning
confidence: 99%